Safety and efficacy of Melissa officinalis (lemon balm) on ApoA-I, Apo B, lipid ratio and ICAM-1 in type 2 diabetes patients: A randomized, double-blinded clinical trial. (October 2018) - Asadi, Akbar; shidfar, Farzad; Safari, Mostafa; Malek, Mojtaba; Hosseini, Agha Fateme; Rezazadeh, Shamsali; Rajab, Asadollah; Shidfar, Shahrzad; Hosseini, Sharieh
Highlights: Melissa officinalis extract supplementation significantly increased Apo A-I and reduced TC/ HDL-c and LDL-c/ HDL-c. Melissa officinalis led to significant within group increases in Apo A-I and reduction in TG/HDL-c levels in Mlissa officinalis group. Serum levels of ICAM-1, AST and, ALP significantly decreased in both groups. There was found a significant within group increase in Apo B/Apo A-I and reduction in Apo A-I levels in placebo group. Short term supplementation of Melissa officinalis extract may be useful in management of cardiovascular risk factors in type 2 diabetic patients. Abstract: Background: The purpose of this study was to investigate the safety and effects of Melissa officinalis, a good source of bioactive components, on apolipoprotein (Apo)B, Apo A-I, and their ratio, lipids ratios and intercellular adhesion molecule-1(ICAM-1) in patients with type 2 diabetes. Methods: For the present randomized, double-blinded, placebo-controlled clinical trial, 70 type 2 diabetic patients aged 20–65 years old were randomly assigned to receive hydroalcoholic extract of M. officinalis (HEMO) (700 mg/d) or placebo twice-daily for 12 weeks. Results: There were significant differences in serum Apo A-I, TC/ HDL-c and LDL-c/ HDL-c between the two groups at the end of the study (p < 0.05), but we did not show significant differences in the values for Apo B, Apo B/Apo A-I, TG/HDL-c, ICAM-1 and liver enzymes include AST, ALT, and ALP between the study groups. Although both groups showed a significant reduction in ICAM-1, AST and, ALP (p < 0.05), no significant differences in ICAM-1, AST and, ALP were observed. At end, in M. officinalis group, there was a significant increase in Apo A-I (p = 0.003) and significant reduction in TG/HDL-c (p = 0.05) compared with initial values, as well as in placebo group, there was a significant rising in Apo B/Apo A-I (p = 0.02) and significant reduction in Apo A-I (p = 0.001) compared with baseline values. Conclusions: M. officinalis is safe and effective in improvement of Apo A-I, Apo B/Apo A-I, and lipids ratios as key factors promoting cardiovascular disease (CVD) in type II diabetic patients.